IMPLEMENTASI FATWA MUI NOMOR 8 TAHUN 2011 TENTANG AMIL ZAKAT DALAM PELAKSANAAN TUGAS DAN TANGGUNG JAWAB AMIL - Nimas Nabila Ikhsan; Ayu Kholifah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
MUI Fatwa Number 8 of 2011 regulates the duties of zakat collectors in the collection, maintenance, distribution, and reporting of zakat. However, many people still distribute zakat maal directly to mustahik without going through official institutions. This research aims to evaluate the implementation of the fatwa by LAZISMU Majenang Service Office. Using a qualitative approach with techniques such as observation, interviews, and documentation with LAZISMU and the local community. The data obtained were analyzed through the stages of reduction, data presentation, and conclusion drawing. The research results show that the amil have carried out their duties according to the fatwa, although not optimally due to internal constraints such as personnel turnover due to other job offers, which negatively impact the collection, maintenance, and distribution of zakat. Efforts to improve the performance of amil have been carried out through the principles of Good Corporate Governance, training, and capacity development that have been implemented. However, the effectiveness of these efforts needs to be supported by more optimal utilization of digital technology, considering that its current use is still limited.